Molecular basis of polyadenylated RNA fate determination in the nucleus - Andrii Bugai; Ulrich Hohmann; Ana Lorenzo; Max Graf; Laura Fin; Jérôme O. Rouvière; Laszlo Tirian; Yuhui Dou; Marion Le Rest; Patrik Polák; Dennis Johnsen; Lis Jakobsen; et al. (Nature, 2026)
Abstract Eukaryotic genomes generate a plethora of polyadenylated (pA + ) RNAs 1,2 , which are packaged into ribonucleoprotein particles (RNPs). To ensure faithful gene expression, functional pA + RNPs, including protein-coding RNPs, are exported to the cytoplasm, whereas transcripts within non-functional pA + RNPs are degraded in the nucleus 1–4 . How cells distinguish these opposing fates remains unknown. The DExD-box ATPase UAP56 (also known as DDX39B) is a central component of functional pA + RNPs, and promotes their docking to the nuclear pore complex-anchored TREX-2 5,6 , which triggers transcript release from UAP56 to facilitate export 7 . Here we reveal that the poly(A) tail exosome targeting (PAXT) connection 8 binds a TREX-2-like module, which releases pA + RNAs from UAP56 for decay by the nuclear exosome. The core of this module consists of a LENG8–PCID2–SEM1 trimer, which we show is structurally and biochemically equivalent to the central GANP–PCID2–SEM1 trimer of TREX-2. Mutagenesis and transcriptomic data demonstrate that the nuclear fate of pA + RNPs is governed by the contending actions of nucleoplasmic PAXT and nuclear pore complex-associated TREX-2, which interpret RNA-bound UAP56 as a signal for RNA decay or export, respectively. As RNA targets of PAXT are generally short and intron-poor, we propose an overall model for pA + RNP fate determination whereby the distinct sub-nuclear localizations of PAXT and TREX-2 govern the degradation of short non-functional pA + RNAs while allowing export of their longer and functional counterparts.